TINJAUAN TENTANG KONSEP NEGARA HUKUM INDONESIA PADA MASA SEBELUM DAN SESUDAH AMANDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Cecep Cahya Supena CahyaSupena (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The establishment of the Indonesian rule of law state which includes the following elements: Government based on law, separation/sharing of powers within the state, guarantee/protection of human rights, and existence of a State Administrative Court, is intended so that the administration of the state and government can run in accordance with the principles the principles of a rule of law state which include: Law Enforcement, Supremacy of Law and Equality Before The Law with the aim of realizing order, justice and prosperity for citizens. The concept of the Indonesian Law State was drawn up based on the 1945 Constitution of the Republic of Indonesia (1945 Constitution) both before and after the amendments to the Body of the 1945 Constitution, in addition to that the Indonesian Law State was also formed based on Laws and Regulations other applicable in Indonesia. Therefore, it can be said that the State of Indonesia in addition to adhering to the Sovereignty of the People also adheres to the Sovereignty of Law.